Muhallil Marriage in Islamic Law and Women’s Rights - Aisyatul Maghfiroh; Ishaq Ishaq; Martoyo Martoyo (Academia Open, 2026)
General Background: Muhallil marriage, conducted after a triple divorce to permit remarriage with a former husband, remains a contested issue in Islamic family law due to its ethical and legal implications. Specific Background: Classical jurisprudence debates its formal validity, while contemporary practices reveal recurring manipulation that places women in vulnerable positions. Knowledge Gap: Existing studies largely address doctrinal legality or socio-legal aspects, with limited integration of feminist jurisprudence and maqasid al-shariah, particularly within the Indonesian context. Aims: This study aims to examine the concept and practice of muhallil marriage through classical and contemporary Islamic legal thought and to critically assess it using feminist jurisprudence and maqasid al-shariah perspectives. Results: Based on a qualitative literature review of fiqh texts, fatwas, religious court decisions, and feminist legal scholarship, the findings indicate that muhallil marriage contradicts the objective of preserving human dignity (ḥifẓ al-‘irḍ) and undermines gender justice within maqasid al-shariah. Feminist jurisprudence identifies the practice as instrumentalizing women for the interests of others. Novelty: The study integrates Jasser Auda’s maqasid framework with feminist jurisprudence, an approach rarely combined in prior research on muhallil marriage. Implications: The findings support the need for reformulating Islamic family law to ensure substantive protection of women’s rights while remaining grounded in the normative objectives of Islamic law. Highlights: The practice conflicts with the objective of preserving human dignity within Islamic legal principles. Gender injustice emerges through the treatment of women as legal instruments in marital arrangements. Integrating maqasid analysis with feminist legal theory offers a comprehensive framework for family law reform. Keywords: Muhallil Marriage, Islamic Family Law, Maqasid Al-Shariah, Feminist Jurisprudence, Women’s Rights